Experiences from attention training techniques among athletes - Moen, F.; Firing, K. (The Sport Journal, 2015)
The purpose of the present study was to investigate how Attention Training Techniques (ATT) affects young athletes in sport. Six athletes who participated in a 12-week ATT training program participated in qualitative interviews that explored their experiences from the program. Our findings indicate that ATT training can influence junior athletes` experiences of being able to switch from a mind wandering state to take executive control of their attention. Secondly, when the athletes experiences that they have executive control of their attention, they are also able to make an attention switch to key points that make the athletes mindful in context. Thirdly, when the athletes experience that they are mindful in context, they experience that they are able to understand themselves at a deeper level and thereby enhance their self-esteem.